Linking surface and subterranean climate: implications for the study of hibernating bats and other cave dwellers. Issue 10 (19th October 2020) - McClure, Meredith L.; Crowley, Daniel; Haase, Catherine G.; McGuire, Liam P.; Fuller, Nathan W.; Hayman, David T. S.; Lausen, Cori L.; Plowright, Raina K.; Dickson, Brett G.; Olson, Sarah H.
Abstract: Caves and other subterranean features provide unique environments for many species. The importance of cave microclimate is particularly relevant at temperate latitudes where bats make seasonal use of caves for hibernation. White‐nose syndrome (WNS), a fungal disease that has devastated populations of hibernating bats across eastern and central North America, has brought renewed interest in bat hibernation and hibernaculum conditions. A recent review synthesized current understanding of cave climatology, exploring the qualitative relationship between cave and surface climate with implications for hibernaculum suitability. However, a more quantitative understanding of the conditions in which bats hibernate and how they may promote or mediate WNS impacts is required. We compiled subterranean temperatures from caves and mines across the western United States and Canada to (1) quantify the hypothesized relationship between mean annual surface temperature (MAST) and subterranean temperature and how it is influenced by measurable site attributes, and (2) use readily available gridded data to predict and continuously map the range of temperatures that may be available in caves and mines. Our analysis supports qualitative predictions that subterranean winter temperatures are correlated with MAST, that temperatures are warmer and less variable farther from the surface, and that even deep within‐cave temperatures tend to be lower than MAST. Effects of other site attributes (e.g., topography, vegetation, and precipitation) on subterranean temperatures were not detected. We then assessed the plausibility of model‐predicted temperatures using knowledge of winter bat distributions and preferred hibernaculum temperatures. Our model unavoidably simplifies complex subterranean environments and is not intended to explain all variability in subterranean temperatures. Rather, our results offer researchers and managers improved broad‐scale estimates of the geographic distribution of potential hibernaculum conditions compared to reliance on MAST alone. We expect this information to better support range‐scale estimation of winter bat distributions and projection of likely WNS impacts across the west. We suggest that our model predictions should serve as hypotheses to be further tested and refined as additional data become available.